Compositions of seed fatty acids in some Astragalus L. taxa from Turkey - Emre, Irfan; Sahin, Ahmet; Turkoglu, Ismail; Yilmaz, Okkes; Bahsi, Muammer; Kursat, Murat (Soc Botanique France, 2011)
Fatty acid composition in mature seeds of nine Astragalus L. taxa were determined by using gas chromatography. Present results indicated that the seed oils of studied taxa have palmitic acid (C16:0), oleic acid (C18:1 n 9), linoleic acid (C18:2 n 6) and linolenic acid (C18:3 n 3) as major fatty acids. Palmitic acid composition of nine Astragalus was found between 8.5 +/- 0.34-15.8 +/- 0.1%. Also, present study reported stearic acid (C18:0) contents of studied Astragalus are more stable (2.2 +/- 0.16-3.4 +/- 0.26%). The highest oleic acid (C18:1 n 9) content was found in A. christianus (41.7 +/- 0.31 %) but it was found at the lowest level in A. asterias (9.1 +/- 0.03 %). In addition, present study determined that investigated Astragalus species have highest linoleic acid (21.0 +/- 0.31-39.4 +/- 1.81%) and linolenic acid (18.9 +/- 0.11-48.9 +/- 0.5%) contents.
Keywords: Astragalus L.; saturated fatty acids; unsaturated fatty acids